Marginal Propensity to Consume in Hungary: The long-term versus Short-term Challenges to Policy Makers - Write, Keith; Shroff, Arpita; Smith, Garry (Journal of Eastern European and Central Asian Research (JEECAR), 2017)
This study uses Hungarian quarterly data from the International Monetary Fund to estimate a distributed lag model whose coefficients allow derivation of the short-run and long-run marginal propensities to consume.  MPCs are main factors determining the consumption, investment, government spending, and export and import multipliers of the economy.  Hungary's economy has stagnated and its policy makers are exploring new ways to manage its economy.  Our model reveals that the numerical value of Hungarian short-run marginal propensity to consume (MPC) is 0.4081181655 and the long-run MPC is 0.9458619.  These results are consistent with the corresponding figures in emerging and advanced economies.  These derived MPCs suggest that Hungarian economic policy makers should use fiscal instruments to bring these macroeconomic variables back to their long-term trend effectively